Adaptive Impedance Tuning Network Using Genetic Algorithm : ITuneGA - Wong, Yan Chiew; Mahmood, Mohd Najid; Mat Ibrahim, Masrullizam; Ahmad Radzi, Syafeeza; Hamid, Nor Nadiah Abdul (Penerbit Universiti, UTeM, 2016)
-